Is always „beautiful is good“: The influence of applicants’ perceived physical attractiveness on decision to invite them to a job interview - Petrauskaitė, Deimantė; Mikuličiūtė, Vita (Psichologija, 2017)
A great number of scientific studies have proven that better personal characteristics are attributed to attractive people rather than less attractive ones. However, a negative effect of perceived physical attractiveness of woman in a managerial position has been noticed. This paradoxical situation usually is explained by the belief stating that an attractive woman does not have certain relevant competencies for a high-level working position. Nevertheless, the findings of recent years’ studies reveal an increase in the number of women in leading positions. It may affect the power of the belief. Therefore, the aim of this study is to evaluate the significance of perceived physical attractiveness and sex on attributing personal characteristics related to work and decision in inviting a potential employee, in applying to managerial and non-managerial positions and to a job interview. The research was based on several parts. The first part was dedicated to selecting four photographs that should be used in the second part of the research. 90 participants took part in this research (mean age 36.06). Participants had to evaluate the attractiveness of men and women in the photographs. Two photographs of men (most attractive, most unattractive) and two photograps of women (most attractive, most unattractive) were selected. The second part of the research was based on an experiment. 85 participants took part in this research (mean age 36.4). Participants were asked to evaluate personal characteristics related to work of four people shown in the photographs and to decide which of these people they would invite to the job interview. One group of participants was told that the person in the photograph is applying for a managerial position, another group stated that he/she is applying for a non-managerial position. The results revealed that the more attractive person is, the more positive personality traits are assigned to him/her regardless of gender or position that he/she were applying for. This research has proved the “beauty is good” belief. The hypothesis that attractive women are evaluated more negatively that unattractive ones when they apply for a managerial position was not confirmed. Also, attractive people are more likely to be invited to a job interview than unattractive ones.
Keywords: physical attractiveness; curriculum vitae; gender differences